2017
DOI: 10.1039/c7nr04620k
|View full text |Cite
|
Sign up to set email alerts
|

Properties of in situ generated gold nanoparticles in the cellular context

Abstract: Gold nanostructures that serve as probes for nanospectroscopic analysis of eukaryotic cell cultures can be obtained by the in situ reduction of tetrachloroauric acid (HAuCl). To understand the formation process of such intracellularly grown particles depending on the incubation medium, the reaction was carried out with 3T3 fibroblast cells in three different incubation media, phosphate buffer, Dulbecco's Modified Eagle Medium (DMEM), and standard cell culture medium (DMEM with fetal calf serum). The size, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 54 publications
3
33
0
Order By: Relevance
“…For intracellular gold nanoparticle formation, all of the constituents (sans chloroauric acid) are innately present in cellular systems. This intracellular gold nanoparticle formation has been demonstrated previously in mammalian cells, however, only through bulk diffusive treatments, lasting more than 24 h, and typically those are in solutions which contain no cell nutrients (such as DPBS) [35][36][37][38][39][40][41][42][43][44][45][46][47] . These treatment scenarios are non-ideal for minimizing the impact on cellular health.…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…For intracellular gold nanoparticle formation, all of the constituents (sans chloroauric acid) are innately present in cellular systems. This intracellular gold nanoparticle formation has been demonstrated previously in mammalian cells, however, only through bulk diffusive treatments, lasting more than 24 h, and typically those are in solutions which contain no cell nutrients (such as DPBS) [35][36][37][38][39][40][41][42][43][44][45][46][47] . These treatment scenarios are non-ideal for minimizing the impact on cellular health.…”
Section: Resultssupporting
confidence: 57%
“…Previous applications for generating gold nanoparticles intracellularly, typically apply 1 mM of ionic gold over time periods >24 h [36][37][38][39][40][41][42][43][44][45][46][47] . However, the amount of formed plasmonic gold nanoparticles were negligible or considerably reduced when the ionic gold was applied diffusively in the previous literature reports either at lower concentrations (0.1 mM 43,44 , 0.25 mM 42 ) or for shorter time periods (12 h 42 , 15 h 45 ). From our application, we were able to confirm the transition of ionic to plasmonic gold through the spectral library obtained from the enhanced darkfield hyperspectral imaging of Au-PEG clusters reduced through the interactions with MCF-7 cells ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These results suggest that NPs aggregate in the perinuclear region in the course of endosomal maturation and multivesicular fusion, but not inside the cell nucleus. These findings agree with previous results on the distribution of Au NPs in cells [11,12,14]. It is noteworthy that the low signal intensity that was found in the cell nucleus region might be originated from Au NPs located in the cytosol volume above or below the cell nucleus.…”
Section: Elemental Distribution Of Au Nps and Cd-based Qds In Single supporting
confidence: 93%
“…laser raster mode). Laser spot sizes are usually equal to or bigger than 4 µm (nominal value of the crater spot size) and laser scan speeds equal to or lower than 15 µm/s [11][12][13][14]. The image is then constructed by ablating parallel lines on the sample surface.…”
Section: Introductionmentioning
confidence: 99%
“…Control synthesis of biocompatible metal nanoparticles using yeast, fungi, bacteria and plants [4,5], encourage the use of mammalian cells to develop nanoparticles. It has been reported that AuNPs can be generated in situ after incubation of Au 3+ with mammalian cell cultures [6]. Furthermore, it has been observed that nanoparticles can be generated inside the epithelial cells and in intact tumor tissues [6].…”
Section: Introductionmentioning
confidence: 99%